Synergy of state support and novel approaches to implementing the diversiﬁcation strategy by defense industry companies - M. M. Musatova (Мир новой экономики)
The study’s aim is to identify the features of interaction between state structures and companies of the military-industrial complex (DIC) in the course of diversification. Many scientific papers devoted to various aspects of this process show the need for its comprehensive study. Russian publications comment on certain aspects of these interactions. However, the approaches and initiatives of the dominant corporations of the military-industrial complex to carry out diversification, being supported by the state, have not yet fallen on the radar of analysis. The author focuses on solving the problem of removing institutional barriers that hinder the scale and direction of diversification. Also, the study updates new solutions for an active policy of stimulating and expanding the production of civilian products. The author identifies the specifics and advantages of unconventional methods in defense companies. The methodological basis of the work is an institutional approach using a structural and logical analysis. The author highlighted the research methods for using of systematization, grouping, comparative analysis. The paper reflects the results of monitoring relevant approaches to implementing the diversification strategy in state defense corporations. The research showed that it has to increase the share of civilian production for the successful implementation of plans as well as to change the fiscal model for the development of the defense industry to an investment-motivational one. The findings and results obtained indicated scientific novelty and may interest in leading defense companies in order to adjust their strategies, as well as to state agencies in the formation of state policy in defense industry diversification.